2015
DOI: 10.1080/21505594.2015.1031437
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro Paracoccidioides brasiliensisbiofilm and gene expression of adhesins and hydrolytic enzymes

Abstract: Paracoccidioides species are dimorphic fungi that initially infect the lungs but can also spread throughout the body. The spreading infection is most likely due to the formation of a biofilm that makes it difficult for the host to eliminate the infection. Biofilm formation is crucial for the development of infections and confines the pathogen to an extracellular matrix. Its presence is associated with antimicrobial resistance and avoidance of host defenses. This current study provides the first description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 51 publications
(69 reference statements)
6
64
0
Order By: Relevance
“…Therefore, their effective adherence contributes to higher speed invasion of host cells, allowing for evasion of the immune system, establishment of the infection, and in the case of Paracoccidioides spp., lead to different clinical manifestations ( Singer-Vermes et al, 1994 ; de Oliveira et al, 2015 ). Another important fact is that P. brasiliensis is able to form biofilm in vitro , which opens up new possibilities in understanding the infection process of these fungi, since biofilm formation is a condition that provides for the pathogen’s protection against drugs and the host’s immune system ( Sardi et al, 2015 ).…”
Section: The Adhesion Process In Pcmmentioning
confidence: 99%
“…Therefore, their effective adherence contributes to higher speed invasion of host cells, allowing for evasion of the immune system, establishment of the infection, and in the case of Paracoccidioides spp., lead to different clinical manifestations ( Singer-Vermes et al, 1994 ; de Oliveira et al, 2015 ). Another important fact is that P. brasiliensis is able to form biofilm in vitro , which opens up new possibilities in understanding the infection process of these fungi, since biofilm formation is a condition that provides for the pathogen’s protection against drugs and the host’s immune system ( Sardi et al, 2015 ).…”
Section: The Adhesion Process In Pcmmentioning
confidence: 99%
“…More recently, it has been reported that P . brasiliensis yeasts are able to form biofilms and that their presence is associated with overexpression of adhesins and enzymes (Sardi et al ., ).…”
Section: Virulence Factorsmentioning
confidence: 97%
“…Growth in a mass increases the resistance of the organisms to environmental stress, their resistance to antifungal activities and also effectively shields them from attack by phagocytes (Williams and Ramage, 2015). Fungi that are capable of forming biofilms are C. albicans (Zelante et al, 2012), C. neoformans, H. casulatum, P. brasiliensis , and A. fumigatus (Ramage et al, 2009; Pitangui et al, 2015; Sardi et al, 2015). …”
Section: Stealthmentioning
confidence: 99%